The achievement gap: Should we rely on SAT scores to tell us anything about it? - Whittington, Dale (Education Policy Analysis Archives, 2004)
Increasing numbers of students taking the SAT have declined to identify their race/ethnicity. I examined the impact of non-respondents on the validity of reported racial/ethnic differences and year-to-year changes in test performance. Using an analysis reported by Wainer (1988) and SAT data from 1996 to 2003, I confirmed Wainer’s findings that non-respondents prevent accurate estimations of group differences based on SAT data. I then explored the impact of College Board press release information on news reports about the achievement gap. I found frequent reports of racial/ethnic differences in SAT scores and year-to-year changes in scores but negligible consideration of non-respondents. Press releases and media reports should include information about non-respondents and their impact on accuracy of reported differences based on race/ethnicity.